1992
DOI: 10.1161/01.res.70.4.856
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of endogenous tumor necrosis factor ameliorates the severity of myosin-induced myocarditis.

Abstract: Tumor necrosis factor (TNF) and interferon gamma (IFN-gamma) are pluripotent cytokines and have multiple functions during the inflammatory response. Using a murine model of autoimmune myocarditis, we studied the role of TNF and IFN-gamma in myocardial inflammation. Neutralizing monoclonal antibodies against TNF-alpha/beta and IFN-gamma were administered to myosin-immunized A/J mice to assess the effect on the severity of myocardial inflammation. Anti-TNF treatment significantly reduced the severity of myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…Deficiencies in IFN-γ and its receptor were found to lead to exacerbated, progressive, and fatal EAM [6,22,38]. IFN-γ-and IFN-γ-induced iNOS were also shown to limit the expansion of α-MyHC-reactive CD4 + T cells in EAM [18,34,39]. Finally, T-bet−/− mice, which are impaired in Th1 differentiation, exhibited enhanced disease severity [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiencies in IFN-γ and its receptor were found to lead to exacerbated, progressive, and fatal EAM [6,22,38]. IFN-γ-and IFN-γ-induced iNOS were also shown to limit the expansion of α-MyHC-reactive CD4 + T cells in EAM [18,34,39]. Finally, T-bet−/− mice, which are impaired in Th1 differentiation, exhibited enhanced disease severity [40].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MHCII expression can be observed on cardiac nonhematopoietic cells during myocarditis in both humans and rodents [13][14][15]. Induction of MHC class II molecules depends critically on IFN-γ, which is dominantly expressed during myocarditis [16][17][18]. Interestingly, IFN-γ plays a dual role in myocarditis.…”
mentioning
confidence: 99%
“…27,28 Thus one might have anticipated that expression of the human TNFRII-Fc would blunt myocarditis in the baboon heart. However, as serum sTNFRII levels only reached B3 times the baseline levels of baboon sTNFRII, we suggest that insufficient TNFRII-Fc serum levels were achieved to block this TNF-dependent process.…”
Section: Direct Injection Of Aav-2 Into Baboon Hearts Cf Mctiernan Et Almentioning
confidence: 99%
“…97 In A/J mice, monoclonal antibody neutralization of TNF-␣ reduced the severity of myocarditis whereas anti-IFN-␥ increased the severity of disease. 98 TNF-␣ is believed to be produced by heartinfiltrating macrophages in the rat model of myocarditis and to be important in cardiovascular diseases. 99 It has been reported that the lack of TNF-␣ receptor (TNF-R) p55 gene expression could interfere with either lymphocyte activation or target organ susceptibility.…”
Section: Influence Of Cytokines On Myocarditis and Th1/ Th2 Immune Rementioning
confidence: 99%